Cutaneous manifestations in Moyamoya angiopathy: a review - Mitri, Fouad; Bersano, Anna; Hervé, Dominique; Kraemer, Markus (European journal of neurology, 2021)
Background and purpose: Moyamoya angiopathy (MA) is a progressive cerebrovascular disease with a poorly understood pathophysiology. It is mainly characterized by progressive bilateral stenosis of the terminal intracranial part of the supraclinoid internal carotid arteries and the proximal parts of the middle and anterior cerebral arteries. This results in early-onset ischemic or hemorrhagic strokes. The disease may be idiopathic (known as Moyamoya disease) or associated with other heritable or acquired conditions, including type 1 neurofibromatosis or other RASopathies, sickle cell disease, Down syndrome, or autoimmune disorders (known as Moyamoya syndrome). Apart from the brain, other organ manifestations including cutaneous ones have also been described in MA patients. Materials and methods: A literature research on PubMed was performed for articles mentioning the cutaneous association in MA and published between 1994 and October 2020. Conclusion: The present review summarizes the cutaneous associations as well as the coincidental dermatological findings seen in MA patients. Those include changes in the epidermis, dermis, or skin appendages for example café-au-lait spots, hypomelanosis of Ito, livedo racemosa, hemangiomas, premature graying of hair, chilblains etc.